Transformational leadership and “flow”: the mediating effects of psychological climate - Linsner, Sarah Herres (Kansas State University, 2009)
While researchers have begun to study “flow” (Csikszentmihalyi, 1975) as it applies to the workplace, little is known about the impact of leadership on followers’ flow experiences. The current study examined the effect of transformational leadership on followers’ experiences of flow. It was hypothesized that transformational leaders would have an indirect effect on flow through their positive influence on psychological climate. Bakker’s (2008) WOLF scale was used to assess work-related flow. Results supported the hypothesis; psychological climate fully mediated the relationship between transformational leadership and flow. Transformational leaders had a strong indirect effect on all three components of work-related flow: intrinsic motivation, work enjoyment, and absorption. It was also hypothesized that each of the five climate dimensions would significantly mediate the leadership-flow relationship. The dimensions were examined simultaneously in a multiple mediator model to identify the unique contribution of each dimension. Results indicated that three dimensions were significant mediators of the leadership-flow relationship: contribution, recognition, and challenge. Because Kahn (1990) found these dimensions to be indicative of psychological meaningfulness, this study builds on other research linking transformational leadership to perceptions of meaning. While transformational leadership strongly predicted all five climate dimensions, two dimensions failed to contribute to the prediction of flow and to the overall mediating effect of climate: role clarity and supportive management. Longitudinal research is needed to validate the causal nature of the findings in this study. By conceptualizing “flow” as a specific form of momentary cognitive engagement, the present study illustrates the applicability of “flow” to the workplace. The findings of this study point to leadership behaviors and climate conditions that are conducive to flow. Managers seeking to improve employee engagement can apply these findings to the workplace.
Keywords: Transformational leadership; Psychological climate; Climate; Flow; Engagement; Psychology, Behavioral (0384); Psychology, Industrial (0624)